2014
DOI: 10.1177/0022034513519801
|View full text |Cite
|
Sign up to set email alerts
|

Novel PAX9 Mutations Cause Non-syndromic Tooth Agenesis

Abstract: PAX9 is a transcription factor expressed in the tooth mesenchyme during tooth morphogenesis. In Pax9-null mice, tooth development is arrested at the bud stage. In humans, heterozygous mutations in PAX9 have been associated with non-syndromic tooth agenesis, predominantly in the molars. Here, we report 2 novel mutations in the paired domain of PAX9, a three-nucleotide deletion (73-75 delATC) and a missense mutation (C146T), in two unrelated Japanese patients with non-syndromic tooth agenesis. The individual wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
1
21
0
1
Order By: Relevance
“…Over 300 genes are expressed and involved in tooth morphogenesis, including MSX1, PAX9, AXIN2, EDA, SPRY2, TGFA, SPRY4, WNT10A, FGF3, FGF10, FGFR2, and BMP4 [23, 55, 56]. Among these genes, PAX9 (paired box gene 9), MSX1 (muscle segment homeobox 1), AXIN2 (axis inhibition protein 2), and EDA (ectodysplasin A) are the most frequently reported genes associated with nonsyndromic hypodontia [6, 5760]. These all have roles in both signalling pathways and in mediating the signal transduction cascades [56].…”
Section: Aetiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Over 300 genes are expressed and involved in tooth morphogenesis, including MSX1, PAX9, AXIN2, EDA, SPRY2, TGFA, SPRY4, WNT10A, FGF3, FGF10, FGFR2, and BMP4 [23, 55, 56]. Among these genes, PAX9 (paired box gene 9), MSX1 (muscle segment homeobox 1), AXIN2 (axis inhibition protein 2), and EDA (ectodysplasin A) are the most frequently reported genes associated with nonsyndromic hypodontia [6, 5760]. These all have roles in both signalling pathways and in mediating the signal transduction cascades [56].…”
Section: Aetiologymentioning
confidence: 99%
“…PAX9 is a transcription factor expressed in the tooth mesenchyme during tooth morphogenesis [60], with mutations in this gene being implicated in arresting tooth development at the bud stage. Heterozygous mutations in PAX9, in humans, have been associated with nonsyndromic tooth agenesis [2].…”
Section: Aetiologymentioning
confidence: 99%
“…Due to the G quadruplex-forming region located near exon 1, which is present in all the known sequenced placental mammals, PAX9 intron 1 serves a key role in splicing efficiency (23,24). As a transcription factor expressed in the tooth mesenchyme during tooth morphogenesis, heterozygous mutations in PAX9 have been associated with non-syndromic tooth agenesis, predominantly in the molars (2528). In the last decade, the abnormal expression of the PAX9 gene, which is associated with the tumorigenesis, development, invasion and metastasis of many types of cancer, was observed in a variety of malignant human tumors (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…[10] PAX9 also plays a role in the absence of wisdom teeth. [11][12][13] Cobourne reported that tooth agenesis appear to represent a complex multifactorial phenotype, which is influenced by several factors including gene function, epigenetic influences, environmental interaction and developing timing. [9] Several studies have been directed to determine the prevalence of congenitally missing upper lateral incisors in different populations.…”
Section: Introductionmentioning
confidence: 99%